The Interlaboratory comparison exercise using OSL personal dosimeters between the LMRI-DEN/UFPE, Brazil, and LCD/LAF-RAM, Nicaragua. (Brazilian Journal of Radiation Sciences, 2022)
The aim of this paper is to present the results obtained in the intercomparison exercise organized by the Ionizing Radiation Metrology Laboratory at the Federal University of Pernambuco (LMRI-DEN/UFPE) and the Radiation Physics and Metrology Laboratory (LAF-RAM) of the National Autonomous University of Nicaragua, Managua (UNAN-Managua). The comparison aimed to assess the technical capabilities of the Dosimetry Calibration Laboratory (LCD) belonging to LAF-RAM for the irradiation of personal dosimeters in terms of Hp(d) magnitudes with a 137Cs radiation beam. The BeO OSL dosimeters were shipped by LMRI-DEN/UFPE to LAF-RAM for irradiation in March 2020. The evaluation of the Z-Score value obtained in the intercomparison was satisfactory for all irradiations of the dosimeters in the Hp (d) magnitude.